In User's Shoes: An Experimental Design on the Role of Perspective Taking in Discovering Entrepreneurial Opportunities - Prandelli, Emanuela; Verona, Gianmario; Pasquini, Martina (Elsevier, 2016)
Research in entrepreneurship has investigated cognitive traits that in addition to stock of information can spur market opportunities. In this paper we focus on a specific cognitive mechanism: user perspective taking, which means assuming the user’s perspective when approaching a market. We specifically deduce two hypotheses that untangle cognitive processes of user perspective taking in an entrepreneurial setting, highlighting how an entrepreneur can enhance her ability to identify market opportunities by putting herself in the user’s mind. User perspective taking can in fact provide the linking and underlying mechanism to develop not only the needed knowledge about a specific market segment but also the motivation to act-as by entering oneself in users’ minds and being able to figure out how to meet their expectations can increase one’s confidence in one’s actions and intrinsic motivation to find an appropriate solution to the needs of those whose perspective has been shared.To validate our conceptual and anecdotal intuitions, we set up one experimental study. The main results show that user perspective taking actually enhances an entrepreneur’s ability to recognize market opportunities. It also shows that prior knowledge measured as technical expertise of the entrepreneur positively moderates the relationship between user perspective taking and opportunity recognition.Overall, we believe that our study makes three main contributions to entrepreneurship research.First and most important, we suggest that user perspective taking represents a new and powerful cognitive variable. While entrepreneurship studies have begun to highlight cognitive properties that characterize entrepreneurs’ alertness, we suggest that user perspective taking adds an important extra dimension. In particular, taking the user’s perspective can enhance entrepreneurs’ creativity by allowing them to better identify latent user needs and to address user needs by recombining and integrating their previous knowledge. User perspective taking lets entrepreneurs identify market opportunities that are not only more innovative, but also more desirable and aligned with user needs.Second, our study shows, on the one hand, how prior knowledge negatively impacts opportunity identification but, on the other, acts as a positive moderating mechanism in the relationship between user perspective taking and opportunity identification. We show that when entrepreneurs are equipped with coherent cumulated expertise they can better leverage their ability to assume the user’s perspective to understand the user’s problems and find a proper solution. Hence, by introducing the interaction between user perspective taking and prior knowledge, we contribute to shed further light on the relationship between an individual’s prior knowledge and her ability to cognitively process information and identify entrepreneurial opportunities.Third, our work provides a contribution to the user innovation literature. By allowing entrepreneurs to overcome cognitive barriers to knowledge transfer and to discover new market opportunities, user perspective taking may be a fungible way to connect entrepreneurs with users. Entrepreneurs’ propensity to take users’ perspective can enhance their ability to recognize opportunities and their chances to create new ventures that match specific market preferences. The stronger this effect the more user perspective taking is combined with prior entrepreneur’s knowledge.We conclude our contribution by discussing the limitations of our studies and by providing some suggestions for promising avenues for future research in the fields of entrepreneurship, perspective taking and user innovation.
Keywords: 53 Ciencias Económicas::5311 Organización y dirección de empresas; ODS 1 - Fin de la pobreza; ODS 5 - Igualdad de género; ODS 9 - Industria, innovación e infraestructura